Análise de parâmetros cinéticos em mulheres com Síndrome da Dor Femoropatelar no gesto de subida de escada - Silva, Danilo de Oliveira [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Patellofemoral Pain Syndrome often affects athletes and sedentary population, causing anterior knee pain that is exacerbated during functional activities such as climbing stairs. Despite its etiology remains inconclusive, it is known that problems occur in the affected lower limb alignment, resulting from changes in local, distal and proximal to the knee. The study of ground reaction and center of pressure displacement during stair climbing is hardly used for Patellofemoral Pain Syndrome analysis, however, identify and understand if there is and how these changes occur is extremely important for Patellofemoral Pain Syndrome understanding. In this context, the aim of this project was investigating kinetic dynamic patterns in women with Patellofemoral Pain Syndrome during stair climbing. 62 women were recruited to participate in the study, 31 with Patellofemoral Pain Syndrome and 31 pain free. The participants performed 5 stair ascents under an instrumented 7 steps stairs with an embedded force platform on the fourth step. Parameters related to the center of pressure and the vertical ground reaction force were extracted...

A Síndrome da Dor Femoropatelar é exacerbada durante atividades funcionais, como subir degraus. Apesar de sua etiologia permanecer indefinida, sabe-se que ocorrem problemas no alinhamento do membro inferior acometido, decorrente de alterações locais, distais e proximais a patela. O estudo das forças de reação do solo e deslocamento do centro de pressão durante a subida de escadas é pouco utilizado para análise da Síndrome da Dor Femoropatelar, entretanto, identificar e entender se existe e como se dão essas alterações é extremamente importante para o entendimento desta disfunção. Neste contexto, este projeto tem como objetivo geral investigar os padrões dinâmicos cinéticos em mulheres com Síndrome da Dor Femoropatelar, durante subida de escadas. Foram recrutadas 62 mulheres para participarem do estudo, 31 com Síndrome da Dor Femoropatelar e 31 assintomáticas. As participantes subiram 5 vezes uma escada instrumentada de 7 degraus, com uma plataforma de força embutida no quarto degrau. Foram extraídos parâmetros referentes ao centro de pressão e da força vertical de reação solo...
Keywords: Fisioterapia; Movimento; Biomecânica; Dor; Articulação patelofemoral; Physical therapy